Representasi Budaya Komunikasi Masyarakat Jawa dan Eropa Dalam Film Guru Bangsa Tjokroaminoto - Selvia Ningsi; Cecep Ibrahim; Marsia Sumule G.; La Ode Herman Halika; La Iba; Eko Harianto; Wa Ode Lusianai (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2023)
The film Guru Bangsa Tjokroaminoto is one of Garin Nugroho's films with a theme related to Javanese and European cultural values ​​during the Dutch East Indies colonial period. Islamic Union. In the film, there are various elements of Javanese culture, including manners in everyday life, speaking, and dressing according to age and strata. This is different from the culture that existed in European society, during the colonial period the Dutch East Indies made the order of social life complicated because in it there were cultural differences between the Javanese and European communities. This study aims to understand the meaning of Jhon Fiske's semiotic television codes, namely the level of reality, the level of representation, and the level of ideology in representing elements of Javanese and European culture. The research method used is descriptive qualitative which can represent, describe and explain based on the facts of the research object. The data analysis technique used is Jhon Fiske's semiotic analysis which explains an event on television based on social codes with the help of the Nvivo application's Thematic Coding content analysis to facilitate data visualization. The results of film analysis in representing Javanese and European culture are two very different cultures that influence each other but still maintain the culture they already have. The results of the analysis obtained are that the Javanese people still maintain and preserve Javanese culture even though they were colonized by Europeans who brought with them European culture and influenced the Javanese people towards their culture. Javanese culture which persisted above the power of the European government during the colonial period made the benchmark that even though it was influenced by outside cultures, the community had to maintain and preserve the cultures that had been passed down from generation to generation.